2002
DOI: 10.1006/dbio.2001.0560
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation at Promoter Regions Regulates the Timing of Gene Activation in Xenopus laevis Embryos

Abstract: The levels of genomic DNA methylation in vertebrate species display a wide range of developmental dynamics. Here, we show that in contrast to mice, the paternal genome of the amphibian, Xenopus laevis, is not subjected to active demethylation of 5-methyl cytosine immediately after fertilization. High levels of methylation in the DNA of both oocyte and sperm are maintained in the early embryo but progressively decline during the cleavage stages. As a result, the Xenopus genome has its lowest methylation content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 40 publications
3
70
0
Order By: Relevance
“…Notably, total methyl-CpG levels in frogs remain fairly constant through the midblastula transition (62). Then total methylCpG levels drop during gastrulation, suggesting that the rate of new methylation decreases or active demethylation increases (62). Consistent with the latter model, we found that endogenous TDG protein was not detectable from fertilization through early gastrulation (until NF stage 10), and then it increased sharply during gastrulation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Notably, total methyl-CpG levels in frogs remain fairly constant through the midblastula transition (62). Then total methylCpG levels drop during gastrulation, suggesting that the rate of new methylation decreases or active demethylation increases (62). Consistent with the latter model, we found that endogenous TDG protein was not detectable from fertilization through early gastrulation (until NF stage 10), and then it increased sharply during gastrulation.…”
Section: Discussionsupporting
confidence: 82%
“…CRL4 Cdt2 -dependent TDG destruction might be important to regulate DNA methylation levels during development. Notably, total methyl-CpG levels in frogs remain fairly constant through the midblastula transition (62). Then total methylCpG levels drop during gastrulation, suggesting that the rate of new methylation decreases or active demethylation increases (62).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental changes in DNA methylation have been comprehensively studied in different organisms (Bogdanović and Veenstra 2009). In contrast to the global wave of demethylation and subsequent gradual remethylation of the mouse zygote Oswald et al 2000), the genome of the amphibian Xenopus laevis maintains high DNA methylation levels throughout early development (Veenstra and Wolffe 2001), although some changes in the DNA methylation content have been reported for a number of developmentally regulated promoters (Stancheva et al 2002). Depletion of the maintenance DNA methyltransferase (DNMT1) in Xenopus results in an early apoptotic phenotype (Stancheva and Meehan 2000;Stancheva et al 2001), and mouse knockouts for Dnmt1 and the de novo DNA methyltransferase (Dnmt3b) are embryonically lethal (Li et al 1992;Okano et al 1999).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that demethylation of Xbra, the frog homolog of fish ntl, plays a role in regulating the timing of Xbra activation. 25 In zebrafish, it has been reported that DNA methylation occurs at the promoter CpG island of ntl during embryogenesis but does not occur during spermatogenesis. 26 Therefore, we were interested in determining whether the maternal ntl allele is methylated during oogenesis and remains transcriptionally inactive during early embryogenesis.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%